Peran Guru dalam Menstimulasi Perkembangan Sosial Emosional Anak di TK Negeri Pembina Kecamatan Kota Timur Gorontalo - Sri Cindi Patuti; Elvian Bakari; Deliyawati Hairi; Indri Handayani H. Dulusea (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
Social emotional development is the process of children learning to manage and express emotions, and interact with others in accordance with social norms and rules in the surrounding environment. This study aims to describe the social-emotional development of early childhood at TK Negeri Pembina Kota Timur, especially in the aspects of social interaction, emotional control, empathy, and independence. This study uses a quantitative descriptive observation method of 9 children aged 4-5 years in class A2, with a checklist observation instrument based on 10 indicators of social emotional development. The results showed that most children were in the “starting to develop” and “developing as expected” categories, especially in the indicators of playing with friends, sharing, expressing feelings, calming themselves, accepting defeat, showing attention, helping friends, and doing simple tasks. However, in the indicators of waiting for their turn and trying new things, children still need special assistance and stimulation. This finding confirms the importance of the role of families and teachers in providing discipline habituation and creating a supportive environment to support children's social emotional development. The implication of this study recommends that teachers and parents be more active in practicing patience, understanding the concept of queuing, and encouraging children's courage in exploring through an appreciative approach.